p-numerical radius inequalities for the tensor product of operators - Frakis, A.; Kittaneh, F.; Soltani, S. (Eurasian Mathematical Journal, 2026)
In this paper, we give several inequalities for the tensor product of two operators involving the p-numerical radius and the Schatten p-norms.